Lack of Educational Facilities and Infrastructure in Indonesia - Belva Saskia Permana; Galuh Nur Insani; Haldini Reygita; Tin Rustini (CV. Rayyan Dwi Bharata, 2023)
Facilities and infrastructure are one of the factors that greatly affect the success of the teaching and learning process, every school must have adequate facilities and infrastructure in order to support a sustainable learning process. It is still a problem in education in Indonesia, namely the inadequate facilities and infrastructure, there are still many schools, especially elementary schools that do not have facilities. The purpose of this study is to determine the causes of problems in facilities and infrastructure and to find out how facilities and infrastructure in related schools. The approach that the author uses in the preparation of this article is a qualitative approach. Then for the method carried out, namely by the method of literature study. Based on this, it can be concluded that there are still many school infrastructure facilities in Indonesia that are inadequate.